Extracellular Production of Pectinase from Bacteria Isolated from Rotten Apples from Lahore, Pakistan - Amanat, Fatima; Yaqoob, Amna; Ali, Asif; Sajjad, Muhammad (BioScientific Review, 2019)
Pectins are intricate blends of polysaccharides which make up around 33% of plantcell wall. Despite of their presence in the greater part of plant body and in other sources, commercial production of pectin is extremely difficult. This is a systematic study that aimed to produce pectinase from bacterial species isolated from rotten apple samples. Zymography and enzyme assay through DNS method were performed to check the pectinolytic activity of bacteria isolated from rotten apple samples. Of all five bacterial species (Serratia marcescens, Klebseilla pneumoniea, Pseudomonas aeruginosa and Escherichia coli) maximum enzyme concentration was showed in Pseudomonas aeruginosa and it was 6.2 U/mL. The major achievement of this study was to screen out the most efficient pectinases producing isolate of Serratia marcescens from rotten apples that has never been reported to produce pectinase, previously.